Neonatal tetanus in the middle Black Sea region of Turkey - Totan, Mehmet; Küçüködük, Şükrü; Dağdemir, Ayhan; Dilber, Cengiz (The Turkish Journal of Pediatrics, 2002)
We retrospectively analyzed 62 cases with neonatal tetanus (NT) seen in the Department of Pediatrics of Ondokuz Mayıs University from 1989 to 2001. Epidemiological characteristics and prognostic factors on survival were investigated. We grouped the patients into two groups, the survivors and those who died. All patients were born in non-hygienic conditions, coming from rural regions. None of the mothers had been immunized against tetanus. The mortality rate was 40% (25 of 62 cases) and the only two poor prognostic factors on survival were age younger than five days at onset and the presence of fever. There was no significant difference between the two groups regarding the other known prognostic factors. Although the NT rate is declining, we must continue to protect against it by strictly enforcing preventive policies, especially in rural regions.